Expressão de SIRT 1 e SIRT 7 no câncer de endométrio - Oppermann, Christina Pimentel (2017)
Introduction: endometrial cancer is the most prevalent gynecological neoplasm in developed countries and the second most prevalent in Brazil, second only to cervical cancer. It corresponds to 5% of cancers in women worldwide. The majority of cases present as initial disease, and surgical treatment is curative. Few treatment options exist for patients with poor prognostic factors and advanced disease, and the process of carcinogenesis in endometrial cancer has not been fully elucidated. Sirtuins are proteins involved in several cellular processes. The family of these proteins is composed of seven sirtuins (SIRT1-SIRT7). They present specific cell locations, acting in a variety of processes, including regulation of gene transcription, genomic stability, metabolic control, cell cycle regulation, and cell survival. Few studies have evaluated the role of sirtuins in endometrial cancer as well as its association with prognostic factors. Objective: to evaluate the expression of SIRT1 and SIRT7 enzymes in histological samples of endometrial carcinoma of patients operated at Hospital São Lucas (Pontifícia Universidade Católica) between January 2000 and December 2015 and associate the expression of these proteins with the pathological staging and prognostic factors. Materials and Methods: we performed a retrospective study evaluating 66 samples of patients with endometrial cancer from January 2000 to December 2015. The expression of SIRT1 and SIRT7 proteins was identified by the immunohistochemical technique and quantified by the Allred score. The expression of these proteins in cancer samples was correlated with the prognostic factors: age, tumor grade, tumor size, myometrial invasion, lymphovascular invasion and pathological staging. Results: SIRT 1 expression was positive in 40.9% of samples and SIRT7 expression in 24.1% of cases. Expression of these proteins did not present a statistically significant association with any of the adverse prognostic factors in endometrial cancer. Conclusions: endometrial cancer samples were positive for both SIRT1 and SIRT7, but without correlation in the study with prognostic factors. Expression of these proteins in samples of endometrial cancer may represent a possible therapeutic target to be developed in future studies.